An Overview on the Protection Measures for Air-Port Protection in High Density Lightning Regions - Tarimer, I.; Kuca, B. (Elektronika ir Elektrotechnika, 2013)
Air-ports belong to structures, which – due to their location and spatial configuration are especially exposed to the lightning flashes. Moreover theirs dynamic character due to stocked air-crafts, variable in time, has an impact on the lightning attachment issues. This aspect is particularly important taking into account low values of lightning current. In the present paper, rolling sphere method on lightning protection is presented and adequate conclusions are formulated. DOI: http://dx.doi.org/10.5755/j01.eee.19.10.5832